Anti-inflammatory effects of lavender and eucalyptus essential oils on the in vitro cell culture model of bladder pain syndrome using T24 cells - Adrienn Horváth; Edina Pandur; Katalin Sipos; Giuseppe Micalizzi; Luigi Mondello; Andrea Böszörményi; Péter Birinyi; Györgyi Horváth (BMC, 2022)
Abstract Background Interstitial cystitis (IC) has a chronic chemical irritation and inflammation of non-bacterial origin in the bladder wall leading to various severe symptoms. There is evidence that chronic inflammation is significantly associated with abnormal urothelial barrier function, epithelial dysfunction. This is the underlying cause of urothelial apoptosis and sterile inflammation. Method The anti-inflammatory effects of lavender and eucalyptus essential oils (EOs) and their main components (linalool and eucalyptol) were investigated in the T24 human bladder epithelial cell line on TNFα stimulated inflammation, at 3 types of treatment schedule. The mRNA of pro-inflammatory cytokines (IL-1β, IL-6, IL-8) were measured by Real Time PCR. Human IL-8 ELISA measurement was performed as well at 3 types of treatment schedule. The effects of lavender and eucalyptus EOs and their main components were compared to the response to NFκB inhibitor ACHP (2-amino-6-[2-(cyclopropylmethoxy)-6-hydroxyphenyl]-4-(4-piperidinyl)-3-pyridinecarbonitrile). Result There is no significant difference statistically, but measurements show that lavender EOs are more effective than eucalyptus EO. Long time treatment (24 h) of both lavender EO and linalool showed higher effect in decreasing pro-inflammatory cytokine mRNA expression than ACHP inhibitor following TNFα pre-treatment. Moreover, both lavender EOs were found to be significantly more effective in decreasing IL-8 secretion of T24 cells after TNFα pre-treatment compared to the ACHP NFκB-inhibitor. Conclusion The lavender EOs may be suitable for use as an adjunct to intravesical therapy of IC. Their anti-inflammatory effect could well complement glycosaminoglycan-regenerative therapy in the urinary bladder after appropriate pharmaceutical formulation.